Developmental evaluation: Bridging the gaps between proposal, program, and practice , Developmental evaluation: Bridging the gaps between proposal, program, and practice - Lawrence, Rachael B.; Rallis, Sharon F.; Davis, Laura C.; Harrington, Karen (Evaluation, 2018)
Developmental evaluation supports grant-funded initiatives seeking innovation and change. Programs born from aspirational grant language and plans often need guidance as they work toward creating workable models for social innovation. This article describes the challenge of designing and implementing complex programs and presents a case that illustrates how a program moves from proposal to practice. The Massachusetts Charter Public School Association Capacity Building Network is a complex intervention, funded by the US federal government, aimed at raising school capacity to serve students with disabilities and English language learners. Developmental evaluation served to bridge the gaps between an aspirational proposal, an ambitious and ambiguous program plan, and emerging practices to serve this population of students. Jointly reviewing our experience in this developmental evaluation, the evaluation team and a program director share important thematic lessons learned about the developmental evaluation approach., Developmental evaluation supports grant-funded initiatives seeking innovation and change. Programs born from aspirational grant language and plans often need guidance as they work toward creating workable models for social innovation. This article describes the challenge of designing and implementing complex programs and presents a case that illustrates how a program moves from proposal to practice. The Massachusetts Charter Public School Association Capacity Building Network is a complex intervention, funded by the US federal government, aimed at raising school capacity to serve students with disabilities and English language learners. Developmental evaluation served to bridge the gaps between an aspirational proposal, an ambitious and ambiguous program plan, and emerging practices to serve this population of students. Jointly reviewing our experience in this developmental evaluation, the evaluation team and a program director share important thematic lessons learned about the developmental evaluation approach.

Developmental Evaluation - Patton, Michael Quinn (The Nonprofit Quarterly, 2006)